Monitoring Kinerja User Akuntan Menggunakan Dashboard Pada Web Based Accounting Online di Perguruan Tinggi - Untung Rahardja; Qurotul Aini; Alfiah Khoirunisa (SATIN - Sains dan Teknologi Informasi, 2018)
Monitoring the performance of the accountant's user in an agency's Web Based Online Accounting is something that must be done so that its performance can be seen. Performance User accountants must be considered at all times to minimize errors made by the user. As well as monitoring the performance of employees in general, this monitoring is deemed necessary to prevent losses between the two parties, both the user and the provider of Web Based Accounting Online. The use of a dashboard on Web Based Online Accounting can be used to monitor user performance. Because the information presented on the dashboard can display things that happen to an Online Web Based Accounting account owned by an agency that includes actions to create, change and delete transactions, and can see if there are other users who log in. The method used in this study is to identify existing problems, then plan what should be done based on the data obtained, and design a system of information delivery to monitor performance. With the existence of this study in order to monitor the performance of employees as users of Web Based Online Accounting is expected to work optimally and not make mistakes that harm both parties.